Premium Rush Co. : Selling, renting, maintaining bicycles/ Adiba Asry ... [et al.] - Asry, Adiba; Khidam, Amirul Ammar; Azman, Siti Sarah; Abu Saffari, Aizul Afzan; Md Nasir, Ammad Firdaus
As for the business, we are providing services like giving rent and maintaining bicycles. Other than that, we also sell bicycles. The services mentioned above will be the only services that we are going to provide. The business will be located at Bandar Seri Alam. To make it more attractive and interesting, we decided to diversify the bicycle in our company. Premium Rush Co has five types of bicycle which are road bicycle, mountain bicycle, cruiser bicycle, BMX bicycle, and tandem bicycle. With this variations customer will have more choices on bicycle that they are interested in.